Cycles of Neglect: A Statutory Review of State Policies Regarding Feminine Hygiene Product Provision During Incarceration - Wood, McKenzie (International journal of offender therapy and comparative criminology, 2025)
Historically, American correctional institutions were designed for men. An increase in incarcerated females has required states to grapple with issues related to menstrual hygiene, including menstrual cycles. While the federal government requires that women and persons who menstruate in federal prisons be supplied with minimal menstrual hygiene supplies, there is no such mandate for menstruators incarcerated in state prisons. We conducted a review and analysis of state legal statutes and Department of Corrections’ (DoC) policies pertaining to menstrual product provision to incarcerated individuals in the United States. We assessed state statutes and policies for product type, amount and quality, requisition process, and cost. Forty-six jurisdictions had policy between state statute or a DoC manual or handbook. Results indicate policies regarding procurement processes and amount provided were vague.